2018
DOI: 10.1002/14651858.cd012597.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Saline irrigation for allergic rhinitis

Abstract: Background Allergic rhinitis is a common condition affecting both adults and children. Patients experience symptoms of nasal obstruction, rhinorrhoea, sneezing and nasal itching, which may affect their quality of life. Nasal irrigation with saline (salty water), also known as nasal douching, washing or lavage, is a procedure that rinses the nasal cavity with isotonic or hypertonic saline solutions. It can be performed with low positive pressure from a spray, pump or squirt bottle, with a nebuliser or with grav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 42 publications
0
63
0
9
Order By: Relevance
“…Studies have shown their efficacy in AR and sinusitis, and meta-analyses support their use [11,29], with hypertonic solutions (e.g. 2.3% NaCl) being apparently more effective than normal saline solutions [8,9,30].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown their efficacy in AR and sinusitis, and meta-analyses support their use [11,29], with hypertonic solutions (e.g. 2.3% NaCl) being apparently more effective than normal saline solutions [8,9,30].…”
Section: Discussionmentioning
confidence: 99%
“…Symptomatic treatment consists of antihistamines and nasal steroids, while allergen immunotherapy is usually performed in more severe/persistent cases [3,4]-in any case, AR usually requires chronic treatment, which raises safety Page 2 of 11 Mitsias et al Clin Transl Allergy (2020) 10:9 concerns about protracted drug usage, leading to the quest for non-pharmacological approaches [5,6]. Among add-on treatments, nasal irrigation (NI) with saline solutions appears to be useful [7][8][9][10][11], as it does not need medical prescription and is considered safe for long-term use [7]. Normal saline is primarily used, although studies have shown increased effectiveness with hypertonic solutions [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Cochrane review published in 2018 included 14 trials and 747 participants 22. Saline volumes ranged from very low to high, with either hypertonic or isotonic saline solution.…”
Section: Indications and Evidencementioning
confidence: 99%
“…Patients with asthma and rhinitis may present respiratory impairment, resulting in unbalance and adaptations in the musculature and/or orofacial structures and stomatognathic functions, due to the presence of nasal obstruction and consequent mouth breathing (1) . The consequences of this unbalance can be observed in the short or long term, such as facial and vocal quality changes, inadequate occlusion, and body posture alterations (2,3) . In addition, mouth breathing exposes the lower airways to the penetration of allergens, irritants and bacterial agents, increasing the risk of asthma exacerbations (4) .…”
Section: Introductionmentioning
confidence: 99%